1984
DOI: 10.1007/bf00330674
|View full text |Cite
|
Sign up to set email alerts
|

Homology is not required for recombination mediated by DNA gyrase of Escherichia coli

Abstract: We have previously shown that DNA gyrase of Escherichia coli can promote recombination between heterologous DNAs in a cell-free system (Ikeda et al. 1982). In the present paper, we have studied the nucleotide sequences of several recombination junctions of lambda-pBR322 recombinants and found that there were not more than three-basepair homologies between the parental DNAs in six combinations of the lambda and pBR322 recombination sites. Based on this and previous results, we concluded that homology was not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…In the in vitro and in vivo analyses, we showed that the length of the homology is only on average about 1.4 base pairs (Naito et al 1984;Shimizu et al 1997). This indicates the virtual absence of any homology.…”
Section: Introductionmentioning
confidence: 84%
“…In the in vitro and in vivo analyses, we showed that the length of the homology is only on average about 1.4 base pairs (Naito et al 1984;Shimizu et al 1997). This indicates the virtual absence of any homology.…”
Section: Introductionmentioning
confidence: 84%
“…(1) Microhomology-independent events are thought to result from errors of topoisomerase and gyrase (Ashizawa et al 1999). Gyrase-mediated exchanges might also contribute to the REP-mediated events described above because gyrase has been found to cause recombination in vitro and in vivo (Naito et al 1984) and is known to bind to REP sequences (Yang and Ames 1988). (2) Microhomology-dependent events are attributed to single-strand annealing because they are stimulated by the RecE and RecT proteins of the Rac prophage (Shiraishi et al 2006).…”
Section: Illegitimate Recombinationmentioning
confidence: 99%
“…4 shows the sequences of junctions in the recombinants and the corresponding sequences of parental genomes. In A351 DNA, a A sequence occurs up to bp 28,368 and then another A sequence begins from bp 31,721 (Fig. 4a).…”
Section: Calf Thymus Topoisomerase II Mediates Recombinationmentioning
confidence: 99%